2006
DOI: 10.1016/j.meatsci.2006.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of postmortem muscle biochemistry to the delivery of consistent meat quality with particular focus on the calpain system

Abstract: Tenderness has been repeatedly reported as the most important quality aspect of meat. However, a number of studies have shown that a significant portion of retail meat can be considered tough. As a consequence, a significant consumer segment is willing to pay a premium for guaranteed tender meat. However, apart from measuring the shear force, there is no reliable method to predict tenderness. Most of the branded meat programs therefore attempt to ensure eating quality by controlling some of the factors that af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
328
0
40

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 527 publications
(376 citation statements)
references
References 94 publications
(106 reference statements)
8
328
0
40
Order By: Relevance
“…Meat texture is generally difficult to evaluate using physico-chemical tests, as texture depends on the state and interactions of different muscle components, especially myofibrillar and connective tissues (Campo et al 2000; Koohmaraie and Geesink 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Meat texture is generally difficult to evaluate using physico-chemical tests, as texture depends on the state and interactions of different muscle components, especially myofibrillar and connective tissues (Campo et al 2000; Koohmaraie and Geesink 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Post-slaughter proteolytic activity is -E-mail: tyler.turner@lmv.slu.se 1141 a natural enzymatic-induced tenderising process involving the breakdown of cross-linkages between muscle myofibrillar proteins. The biochemistry involved during the postslaughter tenderisation process has been reviewed by Koohmaraie and Geesink (2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although m-and m-calpain share many similar characteristics in growing animals, evidence has indicated that only m-calpain is extensively involved in post-mortem proteolysis of bovine tissue (Koohmaraie and Geesink, 2006). This finding was based on the observed post-mortem m-calpain reduction in bovine muscle, whereas m-calpain was stable (Koohmaraie et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations